Systematic Literature Review (SLR): The Application of Balanced Scorecard Strategy on Financial Performance in the Food and Beverage Industry in Indonesia - Desak Nyoman Lia Lestari; Belandina Anita Sere Sihombing; Luk Luk Fuadah (International Journal of Economics Accounting and Management, 2024)
The implementation of the Balanced Scorecard (BSC) strategy in the food and beverage sector holds high relevance, given this sector's significant contribution to Indonesia's economy. Although extensive research has been conducted on BSC, understanding of its impact on financial performance within the Indonesian context remains limited. This study aims to examine the effect of the learning and growth perspective and the customer perspective within the BSC framework on the financial performance of companies in Indonesia's food and beverage sector. Research data was sourced from Google Scholar and Semantic Scholar for publications from 2019 to 2024. Of the 329 articles identified, six were selected as primary data sources for further analysis. The results are expected to provide valuable insights for company management in implementing BSC to enhance financial performance, and serve as a reference for future research in this area. This study employs a survey design by distributing structured questionnaires to respondents from companies in the food and beverage industry. The sampling technique used is stratified sampling, with data analysis carried out through descriptive statistics and simple linear regression. The findings indicate that both BSC perspectives have a positive and significant impact on financial performance, with the learning and growth perspective and the customer perspective each demonstrating significant influence